1999
DOI: 10.1016/s0014-5793(99)01386-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in macrophages by cationic liposomes

Abstract: The effects of liposomes on apoptosis in macrophages were evaluated from DNA content and DNA fragmentation. Cationic liposomes composed of different kinds of cationic lipids induced apoptosis in mouse splenic macrophages and the macrophage-like cell line, RAW264.7 cells. Generation of reactive oxygen radicals from macrophages treated with cationic liposomes was detected using flow cytometry, and further apoptosis was inhibited by the addition of oxidant scavenger, N-acetylcysteine. From these findings, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 25 publications
2
66
0
Order By: Relevance
“…[7][8][9] We first verified the suggestions using DOTAP-or DOTMA-containing liposomes without any cargo. When ROS generation was measured in a time-dependent manner, the increase in H 2 O 2 and LPO levels reached a plateau at approximately 40-60 min after treatment of DOTAP-liposomes (Fig.…”
Section: Cationic Lipid-specific Production Of Ros In Hepg2mentioning
confidence: 98%
See 1 more Smart Citation
“…[7][8][9] We first verified the suggestions using DOTAP-or DOTMA-containing liposomes without any cargo. When ROS generation was measured in a time-dependent manner, the increase in H 2 O 2 and LPO levels reached a plateau at approximately 40-60 min after treatment of DOTAP-liposomes (Fig.…”
Section: Cationic Lipid-specific Production Of Ros In Hepg2mentioning
confidence: 98%
“…6) In addition, cationic liposomes containing DOTAP or stearylamine have been suggested to induce ROS and concomitant apoptosis and/or toxicity in cells. [7][8][9] DOTMA also has the capacity for effective siRNA delivery with other cationic polymers (such as polyethylenimine) or receptor-targeted peptides as binary and ternary complexes. 10,11) In addition to siRNA, DOTMA-containing particles have been used for gene delivery vectors as lipo(poly) plexes or polyplexes.…”
mentioning
confidence: 99%
“…nonetheless, cationic lipids with a higher positive charge density are generally more toxic (14). moreover, some reports on toxicity have found that cationic liposomes with a monovalent positive charge (stearylamine) induced apoptosis and the production of reactive oxygen species (ROS) (15) in the raW264.7 (16) and mouse immature B (WEhi 231) cell lines (17). in in vivo toxicity studies of differently charged liposomes by intratracheal instillation in mice, lipofectamine was found to cause much greater toxicity than DOTAP in a dose-dependent manner, which was associated with ROS generation, while neutral and negative liposomes were not toxic at the relevant concentration (18).…”
Section: Introductionmentioning
confidence: 99%
“…Some in vitro studies have been shown that CL induces cytotoxic effects or apoptosis in several cell types, for example, in phagocytic macrophages or immune cells. 11,12) In addition, other studies have demonstrated that some cationic lipid-based transfection agents induced geneexpression changes in human epithelial cells. 13) However, these investigations are limited owing to the fact that they were concerned only with material-related intrinsic cytotoxicity.…”
mentioning
confidence: 99%